Collaboration of Garut University Community Service Program Students in Sukajaya Village, Malangbong District, Garut with Disdukcapil Garut Regency - Retty Handayani; Sultan Hikmat; Anggi Gantini Ramadanti; Sonia Siti Rochmah; Sabila Khaerunisa Fauziah (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract Stunting is a growth and development disorder in children due to chronic malnutrition and repeated infections characterized by substandard weight and height. Along with the increasing number of stunting cases in Indonesia, especially in Garut Regency, in accordance with the government program, Garut University Community Service Program students collaborated with the local government of the Garut Regency Population and Civil Registration Service (Disdukcapil) to collect data on stunting children. This program is equipped with population data collection for residents who do not have Child Identity Cards (KIA), Family Cards (KK), Birth Certificates and Death Certificates. This activity is carried out considering that Garut Regency is currently in a Stunting Emergency situation. So it is necessary to record correct and accurate data. The method used is in the form of providing services to residents in the Sukajaya Village Hall, Malangbong Garut District. In this activity, it was recorded that 6 people were stunted and 516 population documents were successfully made. Abstrak Stunting adalah gangguan pertumbuhan dan perkembangan anak akibat kekurangan gizi kronis dan infeksi berulang yang ditandai dengan bobot dan tinggi badan dibawah standar. Seiring dengan meningkatnya kasus stunting di Indonesia khususnya di Kabupaten Garut, Sesuai dengan program pemerintah, mahasiswa KKN Universitas Garut mengadakan kolaborasi bersama pemerintah daerah Dinas Kependudukan dan Catatan Sipil (Disdukcapil) Kabupaten Garut untuk melakukan pendataan anak stunting. Program ini dilengkapi dengan pendataan kependudukan warga yang belum memiliki Kartu Identitas Anak (KIA), Kartu Keluarga (KK), Akta lahir dan Akta Kematian. Kegiatan ini dilakukan mengingat Kabupaten Garut saat ini sedang berada dalam situasi Darurat Stunting. Sehingga perlu adanya pencatatan data yang benar dan akuat. Metoda yang digunakan berupa pemberian pelayanan kepada warga yang dilakukan di Aula desa Sukajaya Kecamatan Malangbong Garut. Pada kegiatan ini tercatat ada 6 orang mengalami stunting dan berhasil dibuat kepemilikan dokumen kependudukan sebanyak 516 dokumen.